PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN HARMONI SUITES HOTEL BATAM - Wahyuni, Reni wahyuni; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2021)
This Research aims to examine the effect of service quality and promotion on customer loyalty at Harmoni Suites Hotel Batam. The method used in this study is a quantitative method and samples obtained as many as 120 samples using simple random sampling. And in data processing using SPSS version 25. Data T test results in this study show variable Quality of Service (X-1) has the valuet (2.001) > ttable (1.65765) and the significance value 0.048 <0.05, which means H0 is rejected. So it can be concluded that the service quality variable has a positive and significant effect on customer loyalty at Harmoni Suites Hotel Batam. And Variable Promotion (X2) has a valuet (7.655)>ttable (1.65765) and the significant value of 0,000 < 0.05 which means Ho is rejected, it can be concluded that promotion has a positive and significant effect on customer loyalty of Harmoni Suites Hotel Batam. While the results of the F test show fcount (93.297) > ftable (2.68) with a significance value of 0.000 and or <0.05, which means significant. So we can conclude Service Quality variable (X1) and Promotion (X2) positive and significant effect simultaneously on Customer Loyalty (Y) Harmoni Suites Hotel Batam